UPAYA MENINGKATKAN HASIL BELAJAR MELALUI METODE COOPERATIVE LEARNING TIPE STAD PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK SEMESTER GANJIL KELAS XI TIPTL 2 SMKN 2 KOTA BENGKULU TAHUN PELAJARAN 2018/2019 - Sudirman, Sudirman (UNIB Press, 2019)
ABSTRACTThe aims of this study is to see the effect of using the STAD Cooperative Learning method on students learning outcomes. By using this method, learning activities will be focused on students, and the teacher only acts as a motivator and facilitator. The role of students is more dominant in exploring, finding, and developing their own subject matter. So that, the knowledge they get is no longer from the teachers only but it is come as a result from individual and group study. In this study method, students are expected to be able to develop their abilities and potential so that they can find knowledge as expected in learning objective. The knowledge that they get themselves are more long lasting in their memories rather than they get it from the teachers. The use of STAD Cooperative Learning method make students more directly involved and more active in carrying out the learning process and also it can improve their outcome in Electrical Motor Installation Subject.Keywords: Method, Learning Process, STAD Cooperative Learning Type